Retrospective analysis of problem of formation of professional values of teacher - Sergeyeva, Viktoriia (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the retrospective analysis of the problem of the formation of the professional values of a teacher represented in the scientific works of the Ukrainian and foreign scholars. It has been defined that the realization of a successful pedagogical activity of a future teacher does not only require a certain set of knowledge, skills and habits acquired in the higher educational establishment, a high level of professional competence but also a formed system of professional values and understanding of the essence of his professional activity. It has been found out that the problem of the formation of the professional values of a teacher going back deep into the ancient times attracted the attention of philosophers, pedagogues and educationalists at all the stages of the development of pedagogical science. Different historical periods of the development of society influenced the representation of the problem of the formation of the professional values of a teacher which we find in the works of scholars. However, the following values of a teacher have always been immortal in all the times: love for children, humanity, culture, freedom, justice, humanism, honesty, erudition, spirituality, morality. Thus, the axiological component in the content of the professional and pedagogical training gains a great significance, with the help of which it is necessary to equip future teachers with the theoretical and methodological as well as practical knowledge about the essence of values, their nature, the mechanisms of their development and means of functioning as well as about the fundamental role of the professional and pedagogical values in the professional activity of a modern teacher which characterizes his professional growth and self-improvement.